Effects of TiN single layer coating on the wear of ZTA cutting inserts and surface roughness of workpiece - Ahmad Azhar, Ahmad Zahirani; Mokhtar,, Mokhzani; Ratnam, Mani Maran; Ahmad, Zainal Arifin (Trans Tech Publications Ltd, 2017)
Single layer TiN coated and uncoated zirconia toughened alumina (ZTA) cutting inserts were fabricated and used to machine stainless steel 316 in a turning process. The powders of alumina, yttria partially stabilized zirconia and magnesia were mixed and uniaxially pressed into rhombic cutting tool inserts and subsequently sintered at 1600°C for four hours in air. The inserts were coated with TiN layer using the PVD process. Results of wear area illustrate that the coated ZTA inserts show 66.7% increase in wear resistance compared to uncoated ZTA inserts. Commercially available Si3N4 inserts were used to compare the wear performance. Results of Si3N4 flank wear show a 64% more wear resistance compared to coated ZTA inserts. This may be attributed to the lower strength of coated ZTA cutting insert flank. Therefore, it is shown that single coating of TiN provides a significant advantage in the ZTA cutting performance and better quality surface finish